Homeland’s Discourse - Josephy-Hernández, Daniel E. (2020)
This article concentrates on the discourse employed in Homeland, a television show produced in the United States. After a discourse analysis of three characters and the set- tings of the third season, it is easy to conclude that the show encourages and display stereotypical portrayals of not only the US and the government’s secret-service agencies, but also of Iran and the Middle East in general. It foments an Orientalist image of the Middle-East (the near Orient) as both an exotic place (as explained by Said’s 1978 book Orientalism) and a chaotic, underdeveloped one full of terrorists that must be saved and purged by the United States.